Effects of physical training programs on healthy athletes’ vertical jump height: a systematic review with meta-analysis - Ma, Shuzhen; Xu, Yanqi; Xu, Simao (Journal of Sport Science and Medicine, 2025)
Various physical training programs are widely used to enhance vertical jump height, but their relative effectiveness remains de-bated. This systematic review and meta-analysis evaluate effectiveness of four training methods-weight resistance, plyometric, complex, and routine training-on vertical jump height. A comprehensive search of six databases (PubMed, ERIC, Google Scholar, Web of Science, EBSCOhost, and Scopus) identified rel-evant studies coded based on training type, modality, and out-come measures. Methodological quality and statistical analysis were assessed using PEDro scale and R (version 4.1.3) with the 'meta' package. Eight studies revealed that plyometric training and weight resistance exercise increased vertical jump by 5.2 cm (95% CI: 2.6, 7.7 cm; I² = 4.7%) and 9.9 cm (95% CI: 6.7, 13.5 cm; I² = 0.0%), while improved squat jump by 1.5 cm (95% CI: 0.2, 2.6 cm; I² = 0.0%) and 3.1 cm (95% CI: 0.2, 2.6 cm; I² = 16.9%) compared to routine training. Fifteen studies indicated that plyometric training, weight resistance exercise, and complex training increased countermovement jump by 2.0 cm (95% CI: 1.4, 3.7 cm; I² = 0.0%), 2.2 cm (95% CI: 1.4, 3.7 cm; I² = 0.0%), and 5.0 cm (95% CI: 2.5, 7.6 cm; I² = 0.0%) compared to routine training. Complex training was more effective than weight resistance (2.6 cm; 95% CI: 0.2, 5.5 cm) and plyometric training (2.9 cm; 95% CI: 0.2, 5.8 cm), with no significant difference between weight resistance and plyometric training (0.2 cm; 95% CI:-1.0, 2.0 cm). Heterogeneity was low for most comparisons (I² = 0.0% to 16.9%), indicating consistent results across different in-terventions. This meta-analysis demonstrates that plyometric, weight resistance, and complex training significantly improve vertical, squat, and countermovement jump performance. Weight resistance is effective for vertical and stationary vertical jumps, while complex training is most effective for countermovement jumps.